Prenatal Diagnosis in a Fetus With X-Linked Recessive Chondrodysplasia Punctata: Identification and Functional Study of a Novel Missense Mutation in ARSE - Zhang, Li; Hu, Haoran; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Genetics, 2021)
X-Linked recessive chondrodysplasia punctata (CDPX1) is a rare skeletal dysplasia characterized by stippled epiphyses, brachytelephalangy, and nasomaxillary hypoplasia. CDPX1 is caused by function loss of arylsulfatase E (ARSE, also known as ARSL). Pathogenic mutations in ARSE are responsible for CDPX1 in newborns or adults; however, studies have not fully explored prenatal cases. In the current study, a novel missense mutation (c.265A > G) in ARSE was identified in a fetus with short limbs using whole-exome sequencing (WES). Bioinformatic analysis showed that the variant was pathogenic, and RT-qPCR, Western blot, and enzymatic assays were performed to further explore pathogenicity of the variant. The findings showed that the variant decreased transcription and protein expression levels and led to loss of enzymatic activity of the protein. The novel mutation c.265A > G in ARSE was thus the genetic cause for the phenotype presented by the fetus. The current study presents a prenatal case in Chinese population using functional analysis of ARSE, which helps the family to predict recurrence risks for future pregnancies and provides more information for understanding this rare condition. The findings show that WES is a feasible method for prenatal diagnosis of fetuses with CDPX1.